2022
DOI: 10.1021/acsomega.2c03108
|View full text |Cite
|
Sign up to set email alerts
|

NaCl-Assisted Temperature-Dependent Controllable Growth of Large-Area MoS2 Crystals Using Confined-Space CVD

Abstract: Due to its semiconducting nature, controlled growth of large-area chemical vapor deposition (CVD)-grown two-dimensional (2D) molybdenum disulfide (MoS 2 ) has a lot of potential applications in photodetectors, sensors, and optoelectronics. Yet the controllable, large-area, and cost-effective growth of highly crystalline MoS 2 remains a challenge. Confined-space CVD is a very promising method for the growth of highly crystalline MoS 2 in a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 71 publications
0
10
0
1
Order By: Relevance
“…XPS results clearly reveal that N is doped into MoS 2 and MoN bond is present. [37,38] Figure 4a shows the Raman analysis of both undoped and N 2 -doped MoS 2 and the effect of nitrogen on both frequency and intensity for E 2g 1 and A 1g modes with respect to undoped MoS 2 . It was observed that doped MoS 2 indicates a symmetric shift of both the Raman peaks to a greater frequency rate and increased Raman intensity.…”
Section: Xps Analysis Of Undoped Mos 2 and N-doped Mosmentioning
confidence: 99%
See 1 more Smart Citation
“…XPS results clearly reveal that N is doped into MoS 2 and MoN bond is present. [37,38] Figure 4a shows the Raman analysis of both undoped and N 2 -doped MoS 2 and the effect of nitrogen on both frequency and intensity for E 2g 1 and A 1g modes with respect to undoped MoS 2 . It was observed that doped MoS 2 indicates a symmetric shift of both the Raman peaks to a greater frequency rate and increased Raman intensity.…”
Section: Xps Analysis Of Undoped Mos 2 and N-doped Mosmentioning
confidence: 99%
“…Also, high resolution Mo 3p3/2 spectra of undoped MoS 2 is included in FigureS2, Supporting Information, and it shows the absence of MoN bonding. XPS results clearly reveal that N is doped into MoS 2 and MoN bond is present [37,38]. Figure4ashows the Raman analysis of both undoped and N 2 -doped MoS 2 and the effect of nitrogen on both frequency and intensity for E 2g1 and A 1g modes with respect to undoped MoS 2 .…”
mentioning
confidence: 97%
“…They could be facing upward, upside down, upside down but tilted, or stacked to attain a space-confined manner. 63 Before the heating, the quartz tube is first flushed with a high volume of inert gas for endured time to expel the residue moisture and oxygen inside the tube, to endure the good quality of final products. Next, carrier gases are adjusted accordingly and maintained.…”
Section: Preparation Of Cr X Te Y ...mentioning
confidence: 99%
“… 73 For MOKE, the incident light used is a linearly polarized light (LPL) with known polarization and the change in the imaginary part of the complex optical conductivity is analyzed. 63 The right-circularly polarized component (RCP) and left-circularly polarized component (LCP) resolved from the linearly polarized light experience different phase shifts due to different refractive indices, thus resulting in a rotation of polarization plane, i.e., Kerr rotation ( Figure 4 A). 73 However, the intensity of the light remains unchanged as indicated by the equal lengths of the incident and reflective LPL.…”
Section: Magnetic Characterization Of 2d Materialsmentioning
confidence: 99%
“…第一作者.E-mail: s202026015@emails.bjut.edu.cn 1 引言 二维(2D)TMDCs 由于其在纳米电子器件(如场效应晶体管 [1][2][3][4] 、光电探测 器 [5][6][7][8] 、记忆元件 [9][10][11] )中的潜在应用而引起了研究人员的极大兴趣 [12,13] 。然而, TMDCs 器件的光学和电学性能在很大程度上受到晶界 [14] 和层间材料厚度 [15,16] 的影响。 因此,研究人员尝试采用不同的生长制备策略获得 2D TMDCs(如微 机械剥离法 [17][18][19][20][21] 、液相剥离法 [22][23][24] 、分子束外延法 [25,26] 、激光脉冲沉积法 [27][28][29] 和化学气相沉积法 [30][31][32][33][34][35] ),并对其进行性能研究。在这些方法中,CVD 已被证 明是制备高结晶性 TMDCs 的最有效方法。 MoS 2 作为一种 TMDCs 材料,因其单层结构具备的直接带隙结构而显示的 优异光学性能 [36][37][38][39][40][41] 和优异的电学性能 [42][43][44] 而受到研究人员的青睐。目前,研究人 员利用 CVD 法,通过控制反应温度、气体流量、生长时间和用氯化钠(NaCl) 辅助生长等生长影响因素和衬底工程策略 [45] ,制备 MoS 2 单晶并进行了广泛的研 究 [46,47]…”
unclassified